Recent advances in neoadjuvant chemoradiotherapy in locally advanced rectal cancer - Kawai, Kazushige (J Anus Rectum Colon, 2018)
Preoperative chemoradiotherapy (CRT) has been actively used in Europe and the United States to treat advanced low rectal cancer, and provides excellent local control. In Japan, however, the standard treatment is lateral lymph node dissection, and to date CRT has not been actively used. In recent years, an increasing number of Japanese institutions have been using preoperative CRT to treat locally advanced rectal cancer. In this review, we describe the latest trends in CRT under five headings: short-course or long-course radiation, efforts to improve combined chemotherapy, the addition of preoperative adjuvant chemotherapy, the watch and wait strategy, and the significance of lateral lymph node dissection in patients receiving CRT.